ANALISIS SISTEM PENGENDALIAN MANAJEMEN UNTUK PENINGKATAN KINERJA MANAJEMEN PADA PERUSAHAAN KELUARGA (STUDI KASUS PADA UD. X SIDOARJO) - HIDAYAH, NUR (Jurnal Akuntansi AKUNESA, 2016)
this study aims to determine the management control is applied to the family firm so that it can affect the performance of management. This research is qualitative approach. The object of this research is UD.x that located in Sidoarjo. Data collection methods used were interviews, observation and document analysis. Results from this study indicate that the performance of management improvement achieved is quite affected family company of the Management control is less aware of its existence.